Nowe elementy statusu pracowniczego dyrektora przedsiębiorstwa państwowego - Niedbała, Zdzisław (Wydział Prawa i Administracji UAM, 1983)
New acts of 25 Sept. 1981 have substantially changed the legal position of a State enterprise director. It concerns mainly the situation of a director as the managing organ and as the representative of an enterprise. His proffessional status has also changed. This a resulting, among others, from vesting the employees' council with the competence to appoint and recall the director. A minister supervising the enterprise, called the founding organ, is vested with the same authority. Both organs mentioned above enjoy a reciprocal right to raise objection against decided acts of appointing or recalling the director. Trying the objection is a subject of competence of a law court. Several additional elements consolidating the professional status of the director are created in the new regulation. In particular he is protected against a groundless dismissal. Judicial control of acts of appointing and recalling the director can contribute to limiting as yet arbitrary decisions in nominating for that office. Wide competence of the worker's councils in cases concerning appointing and recalling directors of enterprises are laying grounds for the effective social control of managing and directing processes in State enterprises.
New elements of the professional status of a director of State enterprise